Peningkatan Hasil Belajar IPA Terpadu Siswa Kelas VIII Menggunakan Model Pembelajaran Role Playing - Nining Nuraida Ning; Risnita Risnita; Edo Rohmansyah (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to improve student learning outcomes in the Integrated Science subject class VIII A, Al-Hidayah Tanjung Jabung Timur by using a Role Playing learning model with a KKM of 75%, the formulation of the problem that researchers take according to the title is What is the effectiveness of the learning model Role Playing, to improve student learning outcomes in integrated science subjects. This type of research is Classroom Action Research (CAR). This research was conducted at MTs Al-Hidayah Tanjung Jabung Timur in 2022/2023 with research subjects from class VIII A students, 13 students. This research was divided into two cycles, cycle I consisted of two meetings and cycle II consisted of two meetings. The stages of each cycle consisted of planning/observation and reflection. Data collection instruments used were tests, observation sheets and questionnaires. Data analysis was carried out quantitatively and qualitatively with a KKM of 75%. The results showed that the application of Role Playing models can improve student learning outcomes. seen from the first cycle shows the percentage value of student success of 53.8%. And in cycle II it shows results with a value of 84.62%. This shows that applying the Role Playing learning model can improve learning outcomes, as evidenced by the results of this study in cycles I and II. With this, the researchers suggest that teachers can apply the Role Playing learning model in the Integrated Science learning process at MTs Al Hidayah Tanjung Jabung Timur. Keywords: Role Playing Learning Model, Learning Outcomes.